(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
Tagger goats are a promising meat breed, with excellentconformation and meat quality, in Nuba Mountains, where it is raisedunder extensive farming conditions. The objectives of this study were tostudy the phenotypic characteristics, husbandry and reproductive andlactation performance of this genotype in Eldaleng area. Mean bodyweight was 22.5 kg. Mean body measurements (cm) were 58.75, 65.9,78.4 and 38.55 for height at withers, heart girth, barrel circumference andback length, respectively. Body weight and measurements were generallysignificantly (P ≤0.001) higher in males than in females and significantly(P ≤0.001) increased with age. Phenotypic correlations between bodyweight and measurements were generally high, and different regressionequations accurately predicted body weight with no significantdifferences at all ages. Animal colours varied greatly. Most animals werekept in all goat ages. Flock size was 21.1 and females dominated flocksand their longevity was higher than males. The animals depended onnatural pastures and grazed on village outskirts. They kidded all the yearround with peaks in April and October. They were weaned at 4.1 monthsold and most of the males were castrated. Puberty, age at first service andage at first kidding were 7.15, 8.4 and 13.1 months, respectively. Kiddingrate was 87%, twining rate was 52.8% and kidding interval was 245.4days. Mean birth weight was 1.35 kg. Mortality rate was 26.5% in kidsand 10.1% in adults. Milk yield was 0.64 kg/day in 156 days.